THE INFLUENCE OF DIFFERENT SWEETENERS ON IN VITRO STARCH DIGESTION IN BISCUITS WITH WHEAT FLOUR AND WHOLE BARLEY FLOUR - GJORE NAKOV; MARKO JUKIĆ; NASTIA VASILEVA; VIKTORIJA STAMATOVSKA; IVAN DIMOV; DALIBORKA KOCEVA KOMLENIĆ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2019)
Digestion of starch affects the glycemic index and it is important to know the percentage of starch digestion (degradation) in the body. The aim of this study was to investigate In vitro starch digestion of biscuits produced from wheat and barley flour in different ratios (100:0, 70:30, 50:50, 30:70, 0:100) with the addition of various sweeteners (sucrose, glucose solution and a mixture of sucrose and a glucose solution). In vitro starch digestion was evaluated after 0, 60, 120 and 180 min. It has been established that digestion of starch increases over time of hydrolysis. The results indicated that all types of biscuits produced from wheat and barley flour (in different ratio) had the slowest In vitro digestion when sucrose was used as a sweetener. The most rapid In vitro digestion was observed when a glucose solution was used as a sweetener, except in biscuits produced from 100% barley flour where the most rapid digestion was noticed for biscuits with a mixture of sucrose and glucose solution.